2021
DOI: 10.1162/pres_a_00391
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Usability of Phone-Based Virtual Reality in Management-Communication Training

Marjorie Zielke,
Djakhangir Zakhidov,
Malavika Prasad Shringarpure
et al.

Abstract: Phone-based virtual reality (VR) is a potentially important delivery medium for management communication training, particularly as hybrid work environments create the need for new ways to deliver training experiences where students can role-play and practice privately with virtual employees. However, few studies have focused on the viability of delivering phone-based VR, particularly in terms of understandability and usability. In this preliminary case study, we utilize a proxy group of business school student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Although preliminary, this pilot study's results offer exciting perspectives to inform future extension initiatives using VR technologies. Even though the VR video series included in this study was solely on manure and mortality management, this educational innovation has shown its flexibility to demonstrate real-world experiences through electronic devices in other areas of agriculture and other disciplines [66][67][68]. The changes in the participants' awareness levels before and after watching the videos prove this technology's capacity and potential to deliver agricultural technical information.…”
Section: Discussionmentioning
confidence: 99%
“…Although preliminary, this pilot study's results offer exciting perspectives to inform future extension initiatives using VR technologies. Even though the VR video series included in this study was solely on manure and mortality management, this educational innovation has shown its flexibility to demonstrate real-world experiences through electronic devices in other areas of agriculture and other disciplines [66][67][68]. The changes in the participants' awareness levels before and after watching the videos prove this technology's capacity and potential to deliver agricultural technical information.…”
Section: Discussionmentioning
confidence: 99%